IMPLEMENTASI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN TERHADAP PERJANJIAN KERJA WAKTU TERTENTU (STUDI PADA PT FANINDO CIPTA PROPERTINDO KOTA BATAM) - Kurniawan, Candra Kurniawan Candra; ibrahim, Ukas (SCIENTIA JOURNAL, 2021)
One part of the labor which is often used in the perpetration of a contract between the company and its employees are Employment Agreement Specific Time still apply to employees who work temporary nature. However the particular company do not tell clearly about Employment Agreement Specific Time and so there are various and misconceptions between the two sides. This study attempts to analyze the obstacles implementation of Employment Agreement Specific Time . This study using methods empirical normative with library research. The method of analysis of the data used namely the qualitative analysis. This study was research in PT. Fanindo Cipta Propertindo in Batam city. The obstacles that occur are on the term of the employment agreement. Workers who have worked for 2 years cannot continue the Employment Agreement Specific Time. The solution is that the labor has ended its work agreement can wait for a period of 30 days and will be re-recruited by the company.